Gold nano-triangles as saturable absorbers for a dual-wavelength passively Q-switched Nd:GYSGG laser. (25th May 2018) - Ma, Baomin; Li, Ping; Chen, Xiaohan; Wang, Lili; Liu, Binghai; Song, Teng
Abstract: In this paper, gold nano-triangles (GNTs) were used as saturable absorbers (SAs) in a dual-wavelength Nd:GYSGG laser for the first time, to our best knowledge. The maximum average output power was 75 mW with the shortest pulse width of 374 ns at pulse repetition rates of 250 kHz, corresponding to a single pulse energy of 300 nJ. The laser operated at dual wavelengths of 1059.6 and 1062.4 nm under a pump power of 8.5 W. Our work demonstrated that GNTs are promising SAs for Q-switching dual-wavelength solid state lasers.